2018
DOI: 10.1186/s40561-018-0061-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reciprocal peer feedback on EFL learners’ communication strategy use and oral communication performance

Abstract: While most studies focus on individual training of oral communication in English as a Foreign Language (EFL), this study took a social constructivist perspective in examining the effect of an interpersonal process, that is, peer feedback, on the development of oral communication performance and communication strategy use. A mobile application was developed to facilitate learners' engagement in discussion tasks, replay their conversation as well as carry out peer feedback. To examine the effect of mobile-assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
1
6
0
2
Order By: Relevance
“…The results are consistent with prior research that examined the effects of mobile-supported scaffolding on face-to-face instruction and showed improvement in learning outcomes through enhanced collaborative learning (Lan et al, 2007), facilitated task interactions (Lys, 2013), and reciprocal peer feedback (Fang, Cassim, Hsu & Chen, 2018). The mobile-supported TBLT designed in the current study appeared to provide supportive learning conditions for students to achieve pronounced gains in vocabulary (54%) and receptive knowledge to comprehend newly learned vocabulary and grammar in context (27%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results are consistent with prior research that examined the effects of mobile-supported scaffolding on face-to-face instruction and showed improvement in learning outcomes through enhanced collaborative learning (Lan et al, 2007), facilitated task interactions (Lys, 2013), and reciprocal peer feedback (Fang, Cassim, Hsu & Chen, 2018). The mobile-supported TBLT designed in the current study appeared to provide supportive learning conditions for students to achieve pronounced gains in vocabulary (54%) and receptive knowledge to comprehend newly learned vocabulary and grammar in context (27%).…”
Section: Discussionsupporting
confidence: 89%
“…As to why the scaffolds did not increase negotiating for meaning, it is possible that the ability to negotiate requires additional instruction. According to Nakatani (2010) and Fang et al (2018), learners may lack the language knowledge to negotiate for meaning in communication tasks and thus may need consciousness-raising and additional training. These findings provide developmental implications that when learners were scaffolded in a challenging task they would actively adjust their language use during the conversational interaction, which suggested they were working toward the appropriation of L2 knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The findings illustrated that mobile-based feedback monitored learners' oral production and the learners received corrective feedback that enhanced their overall communication performance (Fang, Cassim, Hsu, & Chen, 2018). Another study reported that teacher-based feedback, which involved the "praisecriticism suggestion" supported the development of learners' OECSs performance (Mulualem et al, 2019;Wang et al, 2017Wang et al, , 2018.In some EFL contexts, like in Indonesia, teacher feedback boosted learners' oral skills development (Saefurrohman, 2018).…”
Section: Figure 6 Assessment Methodsmentioning
confidence: 96%
“…Strategi lebih ke arah implementasi sebuah program dijalankan secara efektif dan efisien dengan memperhitungkan berbagai peluang yang mendukung serta mencermati hambatan yang menjadi penghalang. Dikemukakan Fang et al (2018) strategi komunikasi yang tepat dapat mengurangi biaya tinggi serta mendorong lancarnya kegiatan. Karena itu, strategi komunikasi perlu dipersiapkan matang melalui riset komunikan, media, dan pesan.…”
Section: City Branding Dan Strategi Komunikasiunclassified